Patient-centred care for addiction treatment: a scoping review protocol. Issue 12 (27th December 2018) - Marchand, Kirsten; Beaumont, Scott; Westfall, Jordan; MacDonald, Scott; Harrison, Scott; Marsh, David C; Schechter, Martin T; Oviedo-Joekes, Eugenia
Abstract : Introduction: Substance use disorders are chronic conditions that require a multidimensional treatment approach. Despite ongoing efforts to diversify such treatments, evidence continues to illuminate modest rates of treatment engagement and perceived barriers to treatment. Patient-centred care (PCC) is one approach that may strengthen the responsiveness of treatments for people with problematic substance use. The aim of this scoping review is to explore how the principles of PCC have been implemented and operationalised in healthcare settings for people with problematic substance use. Methods and analysis: This scoping review follows the iterative stages of the Arksey and O'Malley framework. Both empirical (from Medline, Embase, PsycINFO, CINAHL and ISI Web of Science) and grey literature references will be considered if they focused on populations with problematic substance use and described or measured PCC or one of its principles in a health-oriented context. Two reviewers will independently screen references in two successive stages of title/abstract screening and then full-text screening for references meeting title/abstract criteria. A descriptive overview, tabular and/or graphical summaries, and a directed content analysis will be carried out on extracted data. This scoping review has been registered with Open Science Framework (https://osf.io/5swvd/ ). Ethics and dissemination: This review will systematically examine the extent and nature of existing evidence of PCC in addiction research and clinical practice. Such evidence will contribute to the operationalisation of PCC for people with problematic substance use. A multidisciplinary team has been gathered to represent the needs of people with problematic substance use, healthcare providers and decision-makers. The team's knowledge users will be engaged throughout this review and will participate in dissemination activities (eg, workshops, presentations, publications, reports).